2001
DOI: 10.1002/jsfa.924
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and metabolism of 14C‐labelled proanthocyanidins from carob (Ceratonia siliqua) pods in the gastrointestinal tract of the rat

Abstract: The aim of the work was to study the binding, degradation and metabolism of dietary condensed tannins in the gastrointestinal tract of an omnivore. Young pods of carob (Ceratonia siliqua L) were radiolabelled by in vivo feeding of 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…In fact, Terrill, Waghorn, Woolley, McNabb, and Barry (1994) showed that polymeric CT are poorly recovered after their transit though the rumen. However, Makkar, Becker, Abel, and Szegletti (1995) demonstrated that rumen microorganisms do not hydrolyse CT. Conversely, studies in rats and humans indicated that CT are not inert within the gut, but undergo structural modifications operated by the intestinal microflora (Abia & Fry, 2001;Déprez et al, 2000). Nevertheless, the effect of dietary CT on meat oxidative stability may be indirect, through the interaction between CT with other antioxidants compounds or with pro-oxidants compounds present in meat.…”
Section: Meat Lipid Oxidationmentioning
confidence: 96%
“…In fact, Terrill, Waghorn, Woolley, McNabb, and Barry (1994) showed that polymeric CT are poorly recovered after their transit though the rumen. However, Makkar, Becker, Abel, and Szegletti (1995) demonstrated that rumen microorganisms do not hydrolyse CT. Conversely, studies in rats and humans indicated that CT are not inert within the gut, but undergo structural modifications operated by the intestinal microflora (Abia & Fry, 2001;Déprez et al, 2000). Nevertheless, the effect of dietary CT on meat oxidative stability may be indirect, through the interaction between CT with other antioxidants compounds or with pro-oxidants compounds present in meat.…”
Section: Meat Lipid Oxidationmentioning
confidence: 96%
“…This may also contribute to the lower number of metabolites and to the lower extent of metabolism of long-chain condensed catechins. In contrast, the low degree of polymerization of condensed catechins supports their degradation, especially in the caecum, resulting in an accumulation of polar phenolic compounds (Abia and Fry 2001;Levrat et al 1993).…”
Section: Transformation Of Condensed Catechins By Colonic Microbiotamentioning
confidence: 96%
“…In vivo, hydrolysis of procyanidins B2 and B5 to epicatechin has been reported in isolated rat small intestine [128]. The degree of polymerisation of proanthocyanidins has also been reported to decrease in rat small intestine [129]. Nevertheless, other in vivo findings suggest that oligomeric proanthocyanidins are not depolymerised into monomeric flavan-3-ols to any extent during passage through the stomach and gastrointestinal tract in rats, although trace quantities of procyanidin B1, B2, B3 and B4 dimers and the C2 trimer have been detected in urine [124].…”
Section: Gastric and Small Intestine Metabolism And Absorptionmentioning
confidence: 97%